Prosecuting the Holocaust : British investigations into Nazi crimes, 1944-1949. - Great Britain. War Office; National Archives (Great Britain) (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2018)
Drawn from The National Archives (UK) and United States Holocaust Memorial Museum, this collection contains a wealth of information regarding the British government's efforts to investigate and prosecute Nazi crimes during the period 1944-1949. The evidence gathered sheds light on almost every aspect of the Holocaust, from the concentration camp system to the mass murder of the “incurably sick” in psychiatric hospitals. More importantly, it gives a voice to the victims of these atrocities, many of whom testified about their experiences immediately after the war.
Date range: 1944-1949.
Keywords: World War, 1939-1945 -- History -- Sources; War crimes investigation -- Great Britain -- History -- Sources; World War, 1939-1945 -- Atrocities -- Sources; Nazis; Holocaust, Jewish (1939-1945) -- History -- Sources